RANCANG BANGUN ALAT PENJERNIH AIR YANG TERCEMAR LOGAM BERAT Fe, Cu, Zn DALAM SKALA LABORATORIUMRANCANG BANGUN ALAT PENJERNIH AIR YANG TERCEMAR LOGAM BERAT Fe, Cu, Zn DALAM SKALA LABORATORIUM - Andi Syahputra; Sugianto '; Riad Syech (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2015)
A research on design and construction of purification equipment of water contaminated by heavy metals Fe, Cu, and Zn was carried out. The equipment was utilized to purify water sample of Siak River at a distance of 1m from the PT. RICRY of rubber industry in Pekanbaru. Analysis was performed by using Atomic Absorption Spectrophotometer (AAS). The analysis results showed that the concentration of Cu, Fe and Zn before filtration process sequentially were 0.3809 ppm, 0.0051 ppm, and -0.0012 ppm. After being filtered twice showed an absorption percentage for type I sieve (with carbon) on the heavy metals sequentially were Fe 75%, Zn 14.29% and Cu 10.78%. Sieve type II (without carbon) absorption percentage of each heavy metal were Fe 59.5%, Zn 7.75%, and Cu 0.0%, while the water discharge at the sieve type I (with carbon) obtained an average water discharge of 0.164 645 x 10-2 m3/s, and the sieve type II (without carbon) of 0.17838 x 10-2 m3/s. Based on the result the sieve type I with carbon has a better result for water purification treatment.